Future Trends for Direction in Enterprise Architecture: Systematic Literature Review - Batmetan, Johan Reimon; Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
In the modern business era, enterprise architecture is becoming increasingly important for companies to achieve their business goals. However, designing and implementing an effective enterprise architecture can be challenging, especially due to the ever-increasing complexity of information systems, changing business needs, and pressure to continually improve efficiency and performance. This study aims to analyze the literature review to map future trends in enterprise architecture related to technological developments and business needs. The research method used This study was conducted by conducting a systematic literature search using leading academic databases such as Scopus, Web of Science, and IEEE Xplore. Inclusion and exclusion criteria have been established to ensure that the selected articles are relevant to the topics discussed. Articles that met the inclusion criteria were then analyzed and critically assessed to identify trends in enterprise architecture. The results of this study produce arguments for the importance of enterprise architecture in helping companies to operate efficiently and integrate different systems and applications. The results of this study indicate that the future trends and topics of enterprise architecture help organizations achieve strategic goals and enable companies to adapt quickly to changes in business and technology. This study concludes that future trends in enterprise architecture can help companies adopt future information technology trends in enterprise architecture. The findings in this study have significant practical implications for enterprise architecture practices. Enterprises should take these trends into account when designing and deploying their enterprise architecture, to ensure that they maximize the benefits of the latest technologies and meet changing business needs.